(3cJGH jJVef ceGd GdhOGO hMSf GdXf hLejd GdGYJbGOs - (3CMeO Hf RQhb GdaGSj, RQhb,J (B899 (3g` s
(3ChdgG (B:s
(3CeG HYO abO HdZfi efce cJGHkG jJVef hMSf GdXf hLejd GdEYJbGO s
(3BNQgG (B:s
(3aEfgG cdgG eCNhPg ef CMGOjK QShd Gddg Udi Gddg Ydjg hSde GfJgi eG hLO MQakG HdG RjGOI Ch fbUGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs